2006
DOI: 10.1117/12.695785
|View full text |Cite
|
Sign up to set email alerts
|

Microwire fibers for low-loss THz transmission

Abstract: In this paper, we will investigate microwire fibers for low-loss terahertz transmission. Microwires, air-clad wire waveguides with diameter smaller than the operating wavelength (a few µm), have an enhanced evanescent field and tight wave confinement resulting in a low loss waveguide structure for the terahertz (T-ray) frequency regime. Based on our experimental data for the bulk material absorption of four glasses (F2, SF6, SF57 and Bismuth) and a polymer (PMMA), we calculate the normalized field distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Form birefringence was observed in alternatingly stacked structures of two different dielectric materials with sub-wavelength thickness, corresponding to onedimensional photonic crystals, such as two different polymers [59], silicon and air [60], but also for stacks of paper with air gaps in between [61]. Analogously, birefringence was reported for asymmetric hollow-core and polymer fibers [62,63]. Furthermore, polymers reinforced by aligned glass fibers were found to be birefringent [3,4,64] due to the embedded fibers representing sub-wavelength structures along one direction with regard to the relatively large THz wavelengths in the 100 μm range.…”
Section: Birefringence At Thz Frequenciesmentioning
confidence: 60%
“…Form birefringence was observed in alternatingly stacked structures of two different dielectric materials with sub-wavelength thickness, corresponding to onedimensional photonic crystals, such as two different polymers [59], silicon and air [60], but also for stacks of paper with air gaps in between [61]. Analogously, birefringence was reported for asymmetric hollow-core and polymer fibers [62,63]. Furthermore, polymers reinforced by aligned glass fibers were found to be birefringent [3,4,64] due to the embedded fibers representing sub-wavelength structures along one direction with regard to the relatively large THz wavelengths in the 100 μm range.…”
Section: Birefringence At Thz Frequenciesmentioning
confidence: 60%
“…From Fig. 16(b), it can be concluded that the diameter where the fibers enter the microwire operating regime as well as the slope of the convergence of the power fraction strongly depends on the refractive index of the fiber material [123].…”
Section: B Microwiresmentioning
confidence: 94%
“…To obtain more information about the power distribution in the radial direction, the power fraction outside the core is calculated [123]. Fig.…”
Section: B Microwiresmentioning
confidence: 99%
“…Unit cell with periodic boundary conditions have been applied to replicate an array of fibers. We have used the frequency domain solver with tetrahedral mesh (29436 tetrahedrons per unit cell), and considered a loss tangent value of 0.106 at 0.5 THz for F2 glass material loss in our simulations [53]. The unit cell is excited with a plane wave and the simulation provides the S-parameters, normalized transmitted and reflected electric field, of the periodic lattice.…”
Section: Experimental and Simulation Setupmentioning
confidence: 99%
“…The fiber pieces are taken from the beginning of a drawing trial prior to achieving equilibrium, thus, the fiber pieces have relatively large radius fluctuation of up to 5 µm. We choose a type of soft glass (F2) as the material of the fiber (circular cross-section), which has refractive index of 2.7 for f ≤ 0.7 THz and loss tangent value of 0.106 at 0.5 THz [53]. Relatively high refractive index (higher than average refractive index of polymers in THz [35]) is necessary for observation of strong magnetic and electric resonances [28].…”
Section: Introductionmentioning
confidence: 99%